How being observed influences preschoolers' emotions following (less) deserving help - Gerdemann, SC; Buechner, R; Hepach, R (Wiley, 2022)
Children sometimes show positive emotions in response to seeing others being helped, yet it remains poorly understood whether there is a strategic value to such emotional expressions. Here, we investigated the influence seeing a peer receive deserving help or not on children's emotions, which were assessed while the peer was present or not. To measure children's emotional expression, we used a motion depth sensor imaging camera, which recorded children's body posture. Five-year-old children (N = 122) worked on a task which yielded greater rewards for them compared to their peer, rendering the peer to be in greater need of help. An adult—who was unaware of the different levels of neediness—then either helped the child who had a lesser need for help (less deserving outcome) or helped the needier peer (deserving outcome). Overall, both children showed a lowered body posture, a more negative emotional expression, after not being helped and an elevated body posture, a more positive emotional expression, after being helped. Seeing their peer (less deservedly) not receive help, and to a lesser extent being observed, blunted children's otherwise positive emotions in response to receiving help. These results are discussed in the broader theoretical context of how children's emotions sometimes reflect their commitment to cooperative relationships with peers.